DEVELOPING STORY BOOK IN ENGLISH FOR PRE SCHOOLERS IN MEDAN - Zelika Rahmi; Amrin Saragih; Sri Minda Murni (Universitas Negeri Medan, 2019)
The objectives of the study was To find out to what extent does the design of story book in English match the preschoolers’ language development, to find out how story book in English designed to cope with the Pre-schoolers, to find out the reason why story book in English designed as it was for pre-Schoolers. The study was research and development. The existing story book was Moo’s Smelly Jumper from David Brown. There were several uncommon words, and the book was not intended in indicators K-13 Curricullum. The researcher wanted to develop a new story book in English for Preschoolers in Medan based on the position of EFL in Indonesia and the preschoolers’ language development in English. The story book was about my pets and me. The researcher develop 6 of pets, cat, rabbit, fish, bird, dog, and rooster. The researcher create the uncommon words to be common word to the preschoolers by presenting the explanation of picture of the object, and the function of the object. the story book was intended to the indicator in K-13 Curricullum. The findings of the study showed that (1) The findings of the existing story book the total score in general were ”2” (the criteria was partially met). And then, preschoolers’ language development, namely 80% matched with Slobin’s theory in Semantic, 76% in Grammatic and 72% preschoolers in Phonology. (2). Based on the validation of the book by the experts, the book got some the revision in the content and in the layout. Finally the book would be : The content : Included the learning outcome, the text was intended to achieve the indicator of K-13 curricullum, namely preschoolers are able to love the pets such as rabbit, cat, dog, birds, and roooster. The layout : the size of page number was not too big, the background was colorfull to attrack The preschoolers’ attention. The series book of “Gunggung is my Dog, Brave Rooster, Miaw the Cheerfull cat, Bird’s sad whistle, and Missing Fish ” had been design to achieved the standard competence which was written in syllabus kemendikbud no 37, “the preschoolers can love the God’s living things” where the theme was “Pets” in the first semester. Based on the findings, it can be concluded that the book was appropriate for Preschoolers in Medan. some suggestion were directed to To teacher of Preschool in Medan supposed giving more attention to the preschoolers’ language development in Medan in doing story telling by using a story book in English, to other researcher, it was suggested that this reseach could be further expanded, elaborated, and explored in other field in ordet to contribute the development, especially in story book, and to all the readers, it was suggested to use this research as the reference for other research in educational research and Development.Keywords : develop, story book, PreSchoolers,